Proceedings of the 17 Th International Symposium on Management (INSYMA 2020) 2020
DOI: 10.2991/aebmr.k.200127.050
|View full text |Cite
|
Sign up to set email alerts
|

Green Concept: Customer Satisfaction in the Service Business

Abstract: This study aims to determine the factors that influence customer satisfaction. The research method used was quantitative. The sampling technique used purposive sampling with 96 respondents. The analysis technique in this study consisted of three stages, namely the first stage of the validity test, the second stage of the reliability test, and the third stage using SEM (Structural Equation Modeling) through SmartPls 3.0 software. The results of this study explained that environmental awareness had a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Subsequently, the green experience creates experiential change for both employees and customers. First of all, the current study confirmed that green experience positively affects customer experience measured by customer satisfaction consistent with Dewi (2020) since the recent shifting of customers' taste toward green service and product (Robinot & Giannelloni, 2010) as it has been increasing concern from the demand side that satisfies intrinsic motivation (Millar et al, 2012). The result implies that green experience is a part of the quality developed by training that improves customer satisfaction (Shen & Tang, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Subsequently, the green experience creates experiential change for both employees and customers. First of all, the current study confirmed that green experience positively affects customer experience measured by customer satisfaction consistent with Dewi (2020) since the recent shifting of customers' taste toward green service and product (Robinot & Giannelloni, 2010) as it has been increasing concern from the demand side that satisfies intrinsic motivation (Millar et al, 2012). The result implies that green experience is a part of the quality developed by training that improves customer satisfaction (Shen & Tang, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…The theory of green purchase behavior (TGPB) suggests ethic‐driven customer decision‐making forms green purchasing behavior (Han, 2020) signaled that GX positively influences CS (Dewi, 2020; Visschers & Siegrist, 2015) since more green‐driven customers would appreciate GX. For example, since there has been an increasing demand for green products and services (Robinot & Giannelloni, 2010), environmental‐friendly products and services have emerged in response to the demand (Mohd Suki, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Konsumen yang membeli produk hijau akan menghargai dan peduli pada atribut hijau pada produk. Tidak hanya itu, adanya atribut hijau akan meningkatkan kepuasan konsumen (Dewi, 2020). Konsumen yang puas, cenderung loyal terhadap produk hijau (Mohd Suki, 2016).…”
unclassified